ANALISIS LIKUIFAKSI AKIBAT GEMPA PADA PEMBANGUNAN TOWER TRANSMISI 150 kV PLTU. LABUHAN ANGIN SIBOLGA - Masriani Endayanti; Semangat M.Tua Debataraja; Junihar Bintang (Prodi Teknik Sipil Fakultas Teknik Universitas Darma Agung, 2020)
One of the impacts caused by an earthquake is the loss of strength of the soil layer due to vibrations called liquefaction. Liquidity generally occurs in poorly graded sand soils. This land was found in the construction of the Electric Steam Power Plant Labuhan Angin Sibolga 150 kV Transmission Tower. Therefore an analysis of the potential liquefaction is important in the design of the transmission tower foundation. Geological threats, especially liquefaction events when large earthquakes in earthquake-prone paths are something that can occur, and can cause extensive damage to buildings and infrastructure. Electric Steam Power Plant Labuhan Angin Sibolga is an earthquake prone area, where a 150 kV Transmission Tower is built with loose sand graded ground texture. To hold the heavy weight of the building on the ground, a solid foundation is needed. If the condition of the soil on the surface is not able to hold the building, then the burden of the building must be forwarded to the hard soil layer below. For this reason, a deep foundation construction is used for the construction of the 150 kV Transmission Tower at the Electric Steam Power Plant Labuhan Angin Sibolga power plant. Planners for the bore pile foundation must be able to bear the vertical force, horizontal force and the moment caused by lateral deformation caused by liquefaction. This load can be obtained from larger and more rigid pile dimensions, so that the pile diameter is 60 cm. Total skin friction ΣTf = 721.80 kg / cm (sondir data), diameter 60 cm.